Contribution and limits of portable X-ray fluorescence for studying Palaeolithic rock art: a case study at the Points cave (Aiguèze, Gard, France). (June 2021) - Chanteraud, Claire; Chalmin, Émilie; Lebon, Matthieu; Salomon, Hélène; Jacq, Kevin; Noûs, Camille; Delannoy, Jean-Jacques; Monney, Julien
Graphical abstract: Highlights: Portable X-ray fluorescence spectrometry limitations investigations in rock art analyses. Better understanding of pXRF spectra by chemiometric approach. Petrographical inspection as crucial first step before geochemical analysis. Testing of quantification models with iron-rich samples and geological standards. pXRF efficiency evaluation in rock art and colouring matirials analyses. Abstract: Analysing the colouring matter used to make prehistoric rock art is essential in order to retrace the chaînes opératoires involved. Despite the well-documented limitations of portable analysis systems, the need to conserve rock art led us to reassess the capabilities of portable X-ray fluorescence (pXRF) spectrometry. Thus, we compared in-situ and laboratory analyses of materials from the Points cave (France), and laboratory pXRF results with analyses obtained using other methods and with reference samples. Results confirmed that current pXRF systems are unable to provide data suitable for elucidating the chaînes opératoires of ferruginous colouring matter.